THE ROLE OF PSYCHOLOGICAL FACTORS IN THE FORMATION OF THE PSYCHOLOGICAL PORTRAIT - Gayupova, Saodat (Журнал иностранных языков и лингвистики, 2023)
The material and the spiritual about students and the specialists in the production of certain roles in the social life on the basis of the special rules on the cooperation between the program and the social group is understood to be ready to fulfill up.